Câmbio e preços no Brasil: uma análise do período 1995 2006 - Habe, James Hiroshi (2009)
Price stability brought to the Brazilian economy a new reality. What was the relationship between price and exchange rate necessary to achieve the new scenario? The exchange rate anchor was the instrument used to reach the price stability. In 1995 managed exchanged rates biased the prices. In 1999 the regime of exchange rate anchor changed to inflation target. The modification in regimes could have altered the relationship between exchange rates and prices. Econometric tests, using monthly exchange rate data, provided evidence of a connection among exchange rates and prices. From 1999 forward, the relations among consumer prices (IPCA) happen through wholesale prices (IPA). The separation of the IPCA in two groups allowed the verification of major influence in monitored prices then in market prices, increasing the IPCA and affecting the monetary policy decision